Reforming European governance: old problems or new principles? - Metcalfe, Les (2001)
The purpose of this article is to examine the reforms currently underway and to consider where they should go in the future. It is important to recognize in doing so that for management reforms in the Commission to be happening at all is a major step forward. Until now, reform of the Commission has been discussed in a ritualistic way without any real expectation that action would follow. Reform debates were confinede to a few limited topics - such as reducing the number of Commissioners - and the protagonists, whether inside or outside the organization, could be confident that little or nothing would happen as a result. To be sure, incremental changes have been made from time to time. New policy responsibilities have been added to the acquis communautaire with little consideration about how best to give effect to them. The general practice has been ad hoc modifications of the original organizational framework rather than systematic reorganization. Since its formation the Commission had experienced organizational grtowth, usually through the creation of additional Directorates General, without organizational development. In other words, its policy responsibilities and (to a lesser extent) its staff and budget had grown without a matching process of developing more sophisticated forms of organization and methods of management based on a fundamental reappraisal of future needs. Ironically, the Santer Commission had begun to do so within the framework of Agenda 2000 but its efforts were overtaken by the events leading to the 1999 crisis (Peterson, 1999; Spence, 2000).
Keywords: European Union